Filifactor alocis brain abscess identified by 16S ribosomal RNA gene sequencing: A case report. Issue 2 (February 2020) - Hishiya, Naokuni; Uno, Kenji; Amano, Masayuki; Asada, Kiyokazu; Masui, Katsuya; Ishida, Yasuhito; Suzuki, Yuki; Hirai, Nobuyasu; Nakano, Akiyo; Nakano, Ryuichi; Kasahara, Kei; Yano, Hisakazu; et al.
Abstract: We report a clinical case of Filifactor alocis brain abscess in an 85-year-old man who had decayed teeth 1 week prior. In this case, the abscess was surgically drained after empirical antibiotics had been initiated. Although the causative organism could not be identified by culture, F. alocis was detected via 16S ribosomal RNA (16S rRNA) gene sequencing of the pus isolated from the abscess. The patient recovered without serious sequelae after surgical drainage and prolonged antibiotic treatment, including metronidazole, ceftriaxone and meropenem for 8 weeks. The findings in this case emphasize that 16S rRNA gene sequencing allows bacterial diagnosis of brain abscess when phenotypic identification fails, such as in cases where patients are undergoing antimicrobial treatment at the time of sampling or where patients are infected with fastidious organisms.